Deformation behavior of aluminum alloy matrix composites reinforced with few-layer graphene. (November 2015) - Shin, S.E.; Bae, D.H.
Abstract: Microstructure and mechanical properties of aluminum alloy 2024 (Al2024)/few-layer graphene (FLG) composites produced by ball milling and hot rolling have been investigated. The presence of dispersed FLGs with high specific surface area significantly increases the strength of the composites. The composite containing 0.7 vol.% FLGs exhibits tensile strength of 700 MPa, two times higher than that of monolithic Al2024, and around 4% elongation to failure. During plastic deformation, restricted dislocation activities and the accumulated dislocation at between FLGs may contribute to strengthening of Al2024/FLG composites.